HUBUNGAN ASUPAN KARBOHIDRAT SEDERHANA, ASUPAN SERAT DAN KEBIASAAN OLAHRAGA DENGAN INDEKS MASSA TUBUH KARYAWAN REKTORAT UNIVERSITAS JENDERAL SOEDIRMAN (UNSOED) - cherinawati, noor (Jurnal Gizi dan Pangan Soedirman, 2018)
This study aim to determine correlation between simple carbohydrates intake, dietary fiber intake, and excercise habbits on body mass index (BMI) of employee. This study used a cross-sectional method. As many as 63 peoples were selected as samples using purposive sampling method. Simple carbohydrate intake and fiber intake were measured using a 2x24 hour recall method, exercise habits were measured using exercise habits questionnaires. BMI was measured using digital scales and microtoise. The result showed an average simple carbohydrates intake 37.8  ± 33.3 g/day , dietary fiber intake 9.7 ± 4.1 g/day, excercise habbits 63.6 ± 77.7 minutes/week. The pearson correlation test showed insignificant relationship between simple carbohydrates intake, dietary fiber intake, and excercise habbits with BMI (p = 0.976, 0.871 and 0.454). Simple carbohydrates intake, dietary fiber intake, and excercise habbits did not relate with BMI head official employee Unsoed.